A human-in-the-loop manufacturing control architecture for the next generation of production systems. (January 2020) - Cimini, Chiara; Pirola, Fabiana; Pinto, Roberto; Cavalieri, Sergio
Highlights: Industry 4.0 technologies are classified according to the physical/cognitive support to humans. Different roles of humans in the smart factory are enabled by technology. The evolution of the human-machine interaction for manufacturing control is discussed. A Social Human-in-the-loop Cyber-Physical Production System architecture is provided. Abstract: In recent years, the introduction of Industry 4.0 technologies in the manufacturing landscape promoted the development of smart factories characterised by relevant socio-technical interactions between humans and machines. In this context, understanding and modelling the role of humans turns out to be crucial to develop efficient manufacturing systems of the future. Grounding on previous researches in the field of Human-in-the-Loop and Human Cyber-Physical Systems, the paper aims at contributing to a deep reflection about human-machine interaction in the wider perspective of Social Human-in-the-Loop Cyber-Physical Production Systems, in which more agents collaborate and are socially connected. After presenting an evolution of manufacturing control organisations, an architecture to depict social interactions in smart factories is proposed. The proposed architecture contributes to the representation of different human roles in the smart factory and the exploration of both hierarchical and heterarchical data-driven decision-making processes in manufacturing.